Are Patients with Subclinical Hypothyroidism at Risk of Depressive Symptoms?. (13th November 2019) - Wildisen, L; Moutzouri, E; Beglinger, S; Syrogiannouli, L; Klöppel, S; Aujesky, D; Rodondi, N; Giovane, C Del; Feller, M
Abstract: Introduction: Subclinical hypothyroidism (SHypo) may be associated with negative health outcomes including depressive symptoms. However, the evidence is conflicting. Methods: We conducted a systematic review and individual participant data (IPD) meta-analysis to assess the association between SHypo and depressive symptoms. We requested IPD from cohorts identified through a systematic literature search. The exposure was thyroid function at baseline (SHypo vs. euthyroid; SHypo defined as thyroid stimulating hormone ≥ 4.5 mlU/L, in combination with normal free thyroxine). The outcome was depressive symptoms at first follow-up, measured on any validated scale. We calculated conversion factors to convert all scores into the Beck Depression Inventory (BDI) scale (range: 0-63, higher scores indicate more depression, minimal clinically important difference: 5). We performed a two-stage IPD meta-analysis. In each cohort, we estimated the mean difference (MD) in depressive symptoms scores between those with SHypo and euthyroid controls adjusted for depressive symptoms at baseline. Further, we adjusted the multivariable linear regression analysis for age, sex, education, and income. We pooled the study effect estimates by using a random effects model. Heterogeneity was assessed by I2. Results: Among six cohorts, we analyzed data from 23, 367 participants (65% female, mean age 60.3±13.2 years, SHypo N = 1, 463). There was no difference in BDI scores between SHypo (10.6) and controls (10.2) at baseline. After a mean follow-up of 8.2±4.3 years, BDI scores did not differ between SHypo and controls (pooled MD 0.3, 95% CI -0.2 to 0.7, I2 14%). Results remained robust in several sensitivity analyses, and no subgroup at increased risk for depressive symptoms could be identified. Conclusions: In this IPD meta-analysis, SHypo was not associated with the development of depressive symptoms. Depressive symptoms do not seem to be an indication for levothyroxine therapy in SHypo. PROSPERO: CRD42018091627 Key messages: Individual studies about the association between subclinical hypothyroidism and depressive symptoms show conflicting results. In this IPD meta-analysis from six prospective cohort studies, patients with subclinical hypothyroidism did not have an increased risk to develop depressive symptoms during a mean follow-up of 8 years.